Numerický model dýchání - Milanovic, Selena (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2017)
Evropská legislativa požaduje snížení počtu zvířat zapojených do laboratorních testů. Současně je známo velmi málo o sekundárních účincích plynných látek (např. Deodorantů, čisticích sprejů) používaných denně v každé domácnosti. Na základě těchto potřeb byla provedena analýza transportu a reziduí částic v dýchacích cestách. Studie byla provedena ve dvou částech: teoretická část - simulace CFD, praktická část ověření. Experimentální část výzkumu je založen na modulu simulátoru plic i-Lung. Modul může být použit i jako pasivní i aktivní simulátor plic.

The number of animals involved in laboratory testing needs to decrease, according to the latest decrees of the European Union. Furthermore, little is known about the secondary effects of gaseous substances (e.g. deodorants, cleaning sprays) used on a daily basis in every household. Based on these pressing necessities, an analysis of particle transport and deposition has been conducted. The study has been conducted on two levels: on a computational basis (CFD simulations) and on a practical basis. The experimental part of the research is based on the functioning of a lung simulator, the i-Lung. The model can be used as a passive simulator as well as an active one.
Numerical model of inhalation
Keywords: plicní simulátor; aerosol; pohyb nanočástic; rezidua nanočástic; lung simulator; aerosol; particle flow; particle deposition